1986
DOI: 10.1073/pnas.83.10.3402
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced mutagenesis in a shuttle vector with a low-background mutant frequency.

Abstract: We have developed a recombinant DNA shuttle vector that permits the molecular analysis of mutations induced in human cells by chemical or physical mutagens. The vector is able to replicate as a plasmid in Escherichia coli and in Epstein-Barr virus (EBV)-transformed human lymphoblastoid cell lines and contains the herpes simplex virus type 1 thymidine kinase gene (HSV tk) as the target for mutagenesis studies. After introduction of the vector into an EBV-transformed lymphoblastoid cell line (LCL-721) by electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…Targeted mutagenesis is also indicated for 1-NOP-induced base substitutions in-VOL. 8,1988 on (Table 3) showed that 13% of the base changes involved A T base pairs, and Kinouchi and Ohnishi (19) recently demonstrated with bacterial nitroreductases that a minor adduct formed by 1-NP involved deoxyadenosine. Therefore, we consider the base substitutions induced by these two carcinogens to be targeted to adducts rather than being the result of apurinic sites (24).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Targeted mutagenesis is also indicated for 1-NOP-induced base substitutions in-VOL. 8,1988 on (Table 3) showed that 13% of the base changes involved A T base pairs, and Kinouchi and Ohnishi (19) recently demonstrated with bacterial nitroreductases that a minor adduct formed by 1-NP involved deoxyadenosine. Therefore, we consider the base substitutions induced by these two carcinogens to be targeted to adducts rather than being the result of apurinic sites (24).…”
Section: Discussionmentioning
confidence: 95%
“…The latter hypothesis is supported by recent studies on the specific mutational changes needed to activate specific oncogenes (7,37,44). Therefore, we and others (3,4,8,9,11,12,14,21,22,30,32,40,41) have begun to study the specific kinds of mutations induced by carcinogens in mammalian cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No mutations were found during initial screening VOL. 7,1987 on May 10, 2018 by guest http://mcb.asm.org/ Downloaded from for 16 of 18 clones examined. Clone 1.11 was chosen for further study.…”
Section: Methodsmentioning
confidence: 99%
“…135 EBV-based episomal vectors bear the additional advantage that they replicate only once per cell cycle, in S phase, along with chromosomal DNA. 136,137 The importance of controlled replication is that it ensures low rates of spontaneous mutation (less than 1/10 5 ) and recombination events, 119,138 although rearrangements of these vectors have rarely been described. 139 Combination of EBV-based episomal vectors with mammalian origins of replication has given them a broader host cell permissiveness.…”
Section: 78mentioning
confidence: 99%